DEVELOPMENT OF AN IDEAL ORGANIZATIONAL STRUCTURE MODEL FOR PRIVATE ISLAMIC HIGHER EDUCATION INSTITUTION: A CASE STUDY AT BHAKTI PERSADA ISLAMIC COLLEGE OF BANDUNG - Supratman, Iman; Al Mighwar, Muhammad; Gunawan, Agus; Nor bin Abd Aziz, Mohd Kasturi; Khairi Syaie, Akhmad Najibul (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
This study is motivated by high expectations and government recognition of the strategic role of Private Islamic Higher Education Institutions (PTKIS), which have not been supported by an optimal organizational structure, particularly at Bhakti Persada Islamic College of Bandung (STAI Bhaper). The lack of adaptive organizational structure hinders the effectiveness of governance and the achievement of institutional goals. This research aims to formulate an ideal organizational structure model which aligns with the dynamic needs of PTKIS and the current regulations. This study employs a qualitative approach, utilizing a case study method, and draws on Henry Mintzberg’s organizational theory, as well as foundation and PTKIS regulations. Data were collected through document analysis, in-depth interviews, and participatory observation. Then, data were analyzed using Albert Humphrey’s SWOT model and validated with Lincoln and Guba’s trustworthiness criteria. The results of the study show that the current organizational structure tends to be bureaucratic with rigid work standards and strict supervision, but has the potential to transform into a more flexible professional organization. The main strength is in the leadership’s commitment and compliance with regulations, while the weakness is in the suboptimal coordination and limited resources. Digitalization and governance reform become strategic opportunities, while internal resistance emerges as the main challenge. This study recommends the implementation of a professional organizational model centered on strengthening managerial capacity, administrative digitalization, and competency-based coordination, which is expected to enhance the governance of STAI Bhakti Persada and become a trademark for other Private Islamic Higher Institutions (PTKIS).